2013
DOI: 10.1111/cdoe.12027
|View full text |Cite
|
Sign up to set email alerts
|

The Caries Assessment and Treatment (CAST) instrument

Abstract: Objectives To describe the ‘Caries Assessment Spectrum and Treatment’ (CAST) instrument, its origin and content, and to provide an example of how results can be reported. Methods The CAST instrument covers the complete range of stages of carious lesion progression: from no carious lesion, through caries protection (sealant) and lesion care (restoration) to lesions in enamel and dentine, the advanced stages of carious lesion progression in pulpal and its consequences on tooth‐surrounding tissue and tooth loss d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
75
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 13 publications
1
75
0
2
Order By: Relevance
“…According to the recent article on CAST Index which was published after the commencement of this study, it stated that if a tooth with secondary caries around sealant is present then the more severe code should be considered i.e., caries (Code 3) over sealant (Code 1). [19] Code 2 (Restoration) was acceptable because it gave a treatment status of the tooth and helped in calculating the "F" component of DMFT index. Many SME's found that, if a tooth which was filled also had caries on another surface it would lead to a problem in CAST scoring.…”
Section: Codesmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the recent article on CAST Index which was published after the commencement of this study, it stated that if a tooth with secondary caries around sealant is present then the more severe code should be considered i.e., caries (Code 3) over sealant (Code 1). [19] Code 2 (Restoration) was acceptable because it gave a treatment status of the tooth and helped in calculating the "F" component of DMFT index. Many SME's found that, if a tooth which was filled also had caries on another surface it would lead to a problem in CAST scoring.…”
Section: Codesmentioning
confidence: 99%
“…Many SME's found that, if a tooth which was filled also had caries on another surface it would lead to a problem in CAST scoring. This issue was sorted in the CAST Index article, [19] which stated that if a tooth with secondary caries with restoration was present then the more severe code was considered i.e., caries (code 3) over restoration (code 2). [19] The only controversy was regarding the designation of in (direct) restorations as it confused many SME's.…”
Section: Codesmentioning
confidence: 99%
See 3 more Smart Citations